Effects of supplemental UV-B radiation on the photosynthesis — physiological properties and flavonoid content of beech seedlings (Fagus sylvatica L.) in outdoor conditions - Láposi, Réka (Acta Biologica Szegediensis, 2005)
Responses of beech seedlings to supplemental UV-B radiation were investigated during three consecutive seasons, in three repeated experiments. Our attention was paid on the alteration of the photosynthetic pigment composition - especially on the xanthophyll cycle pigments - chlorophyll fluorescence parameters, furthermore the accumulation of UV-B absorbing compounds in leaves, the specific leaf mass and leaf water content. The enhanced UV-B radiation generally affected significantly neither photochemical efficiency of PSII, nor photosynthetic pigment composition. UV-B radiation induced some protective mechanisms, thus VAZ-pool increased in beech leaves in every experiment, parallel with the enhancement of non-photochemical quenching. Amount of UV-B absorbing compounds in leaves increased under enhanced UV-B, but no significant changes were observed in the specific leaf mass. Sensitivity of plants to UV-B is largely influenced by other environmental factors and experimental conditions.